Factores ligados a las relaciones parentales, de mayor impacto en el desempeño académico de los niños de sexto grado de la escuela de educación básica “García Moreno” en el barrio san José del batán del cantón Riobamba en el periodo lectivo 2020- 2021 - Ortiz Tuapanta, Karina Isabel (2022)
Parental relationships are the actions carried out by the father and mother focused on the care of their children and educating them to encourage socialization. The problem arises from a lack of control and attention of some parents towards their children as in their affective relationship that shows apathy; for this reason, this thematic appears because the family is a primary axis in the educational accompaniment of their children in such a way it will be reflected in their academic performance knowing that it depends on several factors such as pedagogical, physiological factors and above all the existing family relationship, among others. The objective is to establish the factors that affect their parental relationship and, there fore, their academic performance. For the methodological design, a non-experimental model has been selected in which the subjects were observed in the natural environment without intervention. The research is field research since surveys were applied to 32 parents from a group. The bibliographic research was based on scientifically supporting the characterization of the variables, parental relationships, and academic performance. It is of descriptive type since it intends to describe the characteristics of the factors linked to parental relationships and their influence on academic performance. The survey results tabulated data to make conclusions and recommendations for this research.